The Philosophical Background of Sustainable Development - Piątek, Zdzisława (Problemy Ekorozwoju, 2007)
The present paper discusses the problems connected with the philosophical justification of sustainable development. In this context ecophilosophy is perceived as a new branch of philosophy devoted to the search for theoretical grounds for sustainable development of the human world in a symbiosis with Nature. When we confront the main ideas of ecophilosophy with those of traditional philosophy the basic motivation of philosophical inquiry changes considerably. The new philosophy does not try to justify human exploitation of Nature; by endowing the biosphere with a value per se, but rather contemplates the possibility of a harmonious coexistence of human beings with all other creatures living in the biosphere. Sustainable development is understood as a search for a proper measure of human activity in the environment. It is a mechanism that should be incorporated into the development of western civilization so that our civilization does not choke on its own power. The potential of ecophilosophy depends on the response to the question: “Is the antagonism between Nature and culture inevitable?” This paper tries to demonstrate that it is not.